Bunyamwera virus-induced polypeptide synthesis. - Pennington, T H (1977)
Bunyamwera virus-induced polypeptide synthesis in BSC-1 cell has been studied using polyacrylamide gel electrophoresis and autoradiography. Four virus-induced polypeptides were identified. Their molecular weights were 200 X 10(6) (L), 128 X 10(6) (G1), 31 X 10(6) (G2), and 23 X 10(6) (N). Pulse-chase experiments, short labeling experiments, and experiments using amino acid analogs failed to show evidence of polypeptides processing by proteolytic cleavage. Analysis of the kinetics of synthesis of these polypeptides showed that a clear division into early and late categories could be made, the onset of synthesis of polypeptide N and L rapidly reached a peak and then declined. Polypeptides G1 and G2 were made for several hours; their rate of synthesis then declined. All four polypeptides then continued to be made in relatively small amounts for many hours.